Exploring Sexual Life Experiences and Perceptions of Women with Diabetes: A Qualitative Study - Roza Hoorsan; Minoor Lamyian; Fazlollah Ahmadi; Seyed Ali Azin; Abbas Rahimiforoushani (International Journal of Community Based Nursing and Midwifery, 2022)
Background: Sexual life can be affected through different aspects of living with diabetes. This study aimed to explore the perception and experiences of Iranian women with diabetes at reproductive age regarding the impact of diabetes on their sexual life. Methods: This qualitative study was conducted from August 2018 to February 2019 in five diabetes centers in Tehran. Purposeful sampling method was used to select the participants, and data were collected by in-depth semi-structured interviews. Data were analyzed manually using the conventional content analysis method. Data saturation occurred after interviewing 24 women with diabetes. Results: Three themes were identified. The first theme was “diabetes-related threatened sexual life” with three categories: change in sexual functioning, negative sexual self-evaluation, and concern in sexual relationships. The second theme was “diabetes treatment challenges in sexual life,” which included two categories: adverse effects of diabetes treatment in sexual life and the psychosocial distress related to diabetes treatment. “Couples’ relationship adjustment to diabetes,” was identified as the third theme, including four categories: the need for spouse’s understanding of living with diabetes problems, perceived need for spouse’s support, perceived need for intimacy, and the need to cope with diabetes-related childbearing challenges. Conclusion: According to the participants’ perception and experiences, in addition to sexual problems, diabetes had affected their sexual life through diabetes treatment challenges in sexual life and the way the couples’ relationships adjust to diabetes. Therefore, sexual problems screening and providing counseling services in community-based diabetes care planning are recommended.